Re-material, una alternativa para la vivienda económica autoconstruida, aplicada a un sector de la ciudad de Loja - Apolo Márquez, Karina Alexandra (2014)
he present research work initiated by the concomitant concern between affordable housing and low-quality housing, bearing interest rebut such an assertion, for it has been considered re-use material and genesis of architectural construction. The selection of potentially useful processes wastes for submission to low-tech construction, based on a methodology that classifies globally, sets out the general characteristics, the approximate volume of production in the city, and then proposes strategies for enabled as constructive elements. In the case of application, a diagnosis of homes in a vulnerable sector of the city is the understanding that the only logic is build with what they have on hand since the economic factor is always limited and ends with an architectural proposal defined by the system constructive reused wood pallets and wood from deconstruction of the incipient housing, which exhibits the same progressive, flexible and self-constructed, giving a concrete and accessible response not only economically but also technologically